Prevalence of undiagnosed thyroid dysfunction in correlation with Helicobacter pylori infection: cross-talk between Hashimoto's thyroiditis and Helicobacter pylori - Nearmeen M Rashad; Ahmed F Gomaa (SpringerOpen, 2019)
Background Worldwide, the prevalence of thyroid dysfunction is increasing and it is one of the leading endocrine disorders. The objective of the present study was to assess the prevalence of undiagnosed thyroid dysfunction and its association with Helicobacter pylori (HP) infection and to clarify the association between HP and Hashimoto's thyroiditis. Patients and methods A cross-sectional study was conducted among 300 unrelated patients; 187 patients had normal thyroid function and 113 patients had thyroid dysfunction. The patients were stratified into one of the following five groups based on the reference of the normal thyroid function test; thyroid-stimulating hormone and free thyroxine were used as the screening tests to diagnose thyroid dysfunction. HP antigen in the stool and antibodies against cytotoxin-associated gene A (cag-A), anti-thyroid peroxidase (anti-TPO) antibodies, and anti-thyroglobulin (anti-TG) antibodies were measured. Results Our results show that the prevalence of thyroid dysfunction was found in 37.6% of the studied population. The most frequent dysfunction was subclinical hypothyroidism (44.4%), followed by overt hypothyroidism (20.6%). Interestingly, the prevalence was higher in association with HP infection diagnosed by HP antigen and cag-A antibodies. There was statistically significant positive correlation between HP antigen and anti-TPO as well as anti-TG. Regarding cag-A. There were statistically significant positive correlations between antibodies against cag-A and anti-TG as well as anti-TPO. Interestingly, stepwise linear regression analysis showed that serum thyroid-stimulating hormone levels were independently correlated with free thyroxine, HP. Conclusion The higher prevalence of thyroid dysfunction as observed in the current study was associated with Hashimoto's thyroiditis. Further future multicenter studies with a bigger sample size are needed to validate our findings.